Phosphorylation of PRH/HHEX by Protein Kinase CK2 Regulates Cell Proliferation and Cell Migration in Diverse Cell Types - Jayaraman, Padma-Sheela; Wadey, Kerry S.; George, Sarah J.; Gaston, Kevin (InTechPublication, 2018)
Disruption of the regulatory mechanisms that control cell proliferation and cell migration results in multiple disease states including cancer and leukemia. The Proline-Rich Homeodomain protein (PRH)/haematopoietically expressed homeobox protein (HHEX) is a transcription factor that controls cell proliferation and cell migration in a variety of tissues in the adult and in the embryo. Phosphorylation of PRH by Protein Kinase CK2 (Casein Kinase II) stops PRH from binding to DNA and regulating the transcription of its direct target genes. In leukaemic cells phosphorylation also results in the production of a transdominant-negative truncated PRH phosphoprotein by the proteasome. Phosphorylation of PRH is increased in breast and prostate cancer cells and the consequent loss of PRH activity increases cell proliferation and migration. PRH also regulates the proliferation of vascular smooth muscle cells and CK2-dependent phosphorylation of PRH in these cells accompanies increased cell proliferation during intimal thickening. Thus the ability of PRH to regulate cell behaviour and the control of PRH by CK2 is not limited to a specific cell type or tissue. This raises the possibility that the PRH-CK2 axis could be targeted in a variety of disease states ranging from multiple cancers to the intimal thickening that occurs in vein bypass graft failure and restenosis.